2022
DOI: 10.1177/20406223221091188
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk of herpes zoster in patients with psoriatic disease on systemic treatments: a systematic review and network meta-analysis

Abstract: Background: Numerous previous studies have examined risk of herpes zoster (HZ) in psoriatic disease; however, the results of these studies are conflicting and the relative risks associated with different treatments remain largely unknown. In this meta-analysis, we examined the relative risk of HZ associated with systemic treatments for psoriatic disease. Methods: PubMed, EMBASE, Cochrane Library, and Web of Science databases were searched to identify relevant English-language studies published up to April 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Second, some DMARDs which are known to be associated with HZ reactivation, such as rituximab, mycophenolate mofetil (MMF), and GC [ 36 , 50 ], are not utilized in the treatment arsenal of SpA and therefore were not included in our study. However, Jak-I, which is used in the treatment regimen of PsA and known to be associated with HZ risk [ 11 , 12 , 52 ], was represented in our study and indeed found to be associated with an increased risk of HZ reactivation.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Second, some DMARDs which are known to be associated with HZ reactivation, such as rituximab, mycophenolate mofetil (MMF), and GC [ 36 , 50 ], are not utilized in the treatment arsenal of SpA and therefore were not included in our study. However, Jak-I, which is used in the treatment regimen of PsA and known to be associated with HZ risk [ 11 , 12 , 52 ], was represented in our study and indeed found to be associated with an increased risk of HZ reactivation.…”
Section: Discussionmentioning
confidence: 54%
“…For instance, in the case of AS, a study by Wong et al showed no increase in the incidence of HZ in AS relative to RA (stratified HR = 0.97; 0.58–1.61) [ 9 ], while a Taiwanese study by Wang et al showed no difference in the incidence rate of HZ between AS patients and non-AS controls (adjusted HR = 1.07; 0.84–1.37), with increasing age and cancer serving as significant risk factors for incidental HZ [ 10 ]. In the case of PsA, recent studies mostly discuss the risk of HZ in relation to baseline immunosuppressive treatments [ 11 , 12 ], but a previous study also relying on the CHS database demonstrated that the risk of HZ in an untreated PsA cohort without previous Zostravax ® vaccination is 9.21/1000 patient-years [ 13 ], which is somewhat higher than that in the general population, which is around 7–10/1000 after 50 years of age [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients on interleukin inhibitors had lower or similar HZ incidences to the PsO– cohort, while those on any other therapy had higher HZ incidences than the PsO– cohort. Other studies have reported that HZ risk is increased in patients taking systemic corticosteroids [ 13 , 15 , 16 ], TNF-alpha inhibitors [ 12 , 16 ], JAK inhibitors [ 15 , 16 ], and various combination treatments [ 13 16 ], but not in those on interleukin inhibitors [ 13 , 15 , 16 ], acitretin [ 16 ], or phototherapy [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since many of these treatments target the immune system, patients are at increased risk of infection [ 5 7 ], including herpes zoster (HZ). Various studies have reported that patients with PsO are at increased risk of HZ [ 8 11 ], and that this risk varies by medication class [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%